Predominantly night-time feeding and maternal glycaemic levels during pregnancy - Loy, See Ling (Br J Nutr, 2016)
Little is known about the influence of meal timing and caloric consumption patterns throughout the day on glucose regulation during pregnancy. We examined the association of maternal feeding patterns with glycaemic levels among lean and overweight pregnant women. In a prospective cohort study in Singapore, maternal 24-hour dietary recalls, fasting glucose (FG) and 2-hour postprandial glucose (2HPPG) concentrations were measured at 26-28 weeks’ gestation. Women (n=985) were classified into lean (BMI<23 kg/m(2)) or overweight (BMI≥23 kg/m(2)) group. They were further categorized as predominantly day-time (pDT) or predominantly night-time (pNT) feeders according to consumption of greater proportion of calories from 0700 to 1859h or from 1900 to 0659h respectively. On stratification by weight status, lean pNT feeders were found to have higher FG than lean pDT feeders (4.36±0.38mmol/l vs 4.22±0.35mmol/l, p=0.002); however, such difference was not observed between overweight pDT and pNT feeders (4.49±0.60mmol/l vs 4.46±0.45mmol/l, p=0.717). Using multiple linear regression with confounders adjustment, pNT feeding was associated with higher FG in the lean group (β = 0.16mmol/l; 95% confidence interval (CI) = 0.05 to 0.26; p=0.003), but not in the overweight group (β = 0.02mmol/l; CI = −0.17 to 0.20; p=0.879). No significant association was found between maternal feeding pattern and 2HPPG in both lean and overweight groups. In conclusion, predominantly night-time feeding was associated with higher FG concentration in lean but not in overweight pregnant women, suggesting there may be an adiposity-dependent effect of maternal feeding patterns on glucose tolerance during pregnancy.